The Transatlantic Mediation of Historical Knowledge across the Iberian Empire (c1580-c1640) - Fabien Montcher (E-Spania)
During the time of the Political Turn in the historiography of the Iberian Empire (1580-1640), the parallel careers of the royal historiographer Antonio de Herrera and the would-be historian Francisco Caro de Torres are indicative of the developing mutual relations between global informants and court officials. Departing from the case of the defeat of the English corsair Drake in Panama (1596), this paper examines the processes by which the narrative of such a recent event was negotiated, censored, and reshaped according to the strategies of different court factions, and revived decades later for different professional and political uses. The case of how both Herrera and Caro de Torres used the narrative of Drake's final expedition shows the historical and political enjeux of the writing of recent history across the Atlantic between Madrid and Panama. Finally, both trajectories demonstrate continuity between the political practices royal historiographers in the reigns of Philip II and Philip III and the « hired pens » who would come to foster political action by the means of the politics of history under Philip IV.